Canine T cell lymphoma treated with lomustine, vincristine, procarbazine, and prednisolone chemotherapy in 35 dogs. (16th August 2018) - Morgan, E.; O'Connell, K.; Thomson, M.; Griffin, A.
Abstract : Canine T cell lymphoma has previously been found to be a poor prognostic indicator compared with its B cell counterpart. The cyclophosphamide, doxorubicin, vincristine, and prednisolone protocol is widely accepted as a first line treatment for canine lymphoma. There have been several studies investigating alternative protocols for T cell lymphoma. This study investigated the use of a modified lomustine, vincristine, procarbazine and prednisolone protocol as a first line treatment in 35 dogs with T Cell lymphoma. Median progression free survival (PFS) time for all 35 dogs was 431 days with a 6‐month, 1‐year, 2‐year, and 3‐year PFS of 69%, 54%, 29%, and 12%. Median survival time (MST) was 507 days. Twenty‐nine dogs attained a complete response and had a median PFS time of 509 days. Thirty dogs experienced adverse events during the protocol, with 73% of these being grade 1 or 2. This protocol has shown increased median PFS time and MST compared with previous studies and suggests its use as a first line chemotherapy protocol against canine T cell lymphoma.